Head check resistance of B320 bainitic rail steel grade. (June 2022) - Lesage, T.; Avettand-Fènoël, M.N.; Balloy, D.; Assaf, S.; Cristofari, F.; Secordel, P.
Abstract: This work focuses on the degradation mechanisms of a B320 carbide-free bainitic steel grade rail and of its weld after laboratory tests. The microstructure of the tested rails is investigated, focusing mainly on retained austenite. The Head Check resistance of B320 grade base material is high, notably due to the TRansformation Induced Plasticity (TRIP) effect, inducing a reduction in crack propagation speed. Inside the Heat Affected Zone, a few Head Check defects have been detected and are attributed to a lower retained austenite content coming with a higher Martensite-Austenite Compound content prior to rail testing. In this zone, the transformation process from austenite to martensite following TRIP effect is less pronounced. A novel degradation mechanism is proposed considering the phases contribution in the deformation process of B320 carbide free steel grade. Graphical Abstract: ga1 Highlights: TRIP effect is prevalent in the head check resistance of carbide-free bainitic steel. Crack propagation and wear are competing phenomena. Head check defects occur when most of retained austenite is consumed.